Child participation in school governance: the case of prefects at a primary school in Lesotho - Morojele, Pholoho; Muthukrishna, Nithi (Faculty of Education, University of the Free State, 2011)
This paper draws on literature that has theorised child participation within the sociology of childhood framework to examine how children participate in governance within school spaces. Four children aged between 13 and 17 (in grades six and seven) who serve as prefects at a primary school in Lesotho were participants in this study. Data was collected through a focus group interview and individual semi-structured interviews. The findings of the study indicate that authentic participation of children is limited in the school context. One of the key barriers to participation seems to be a hierarchical and authoritarian school management style. The ethos of control, discipline and authority stifles the process of child participation at the school. The main role of the prefects appears to be ‘policing’ and ‘reporting’ to the school hierarchy. Children’s pursuit of authentic participation denotes that they construct themselves as active social agents, deserving meaningful participation in school governance. The conclusion points to the need to raise critical consciousness for teachers and school management to interrogate their own ideologies about children and childhood, and to challenge the authoritarian hierarchy of school management which impedes children’s meaningful participation.
Keywords: Child participation; Children's voice and agency; School governance in Lesotho; Children's voice and agency in Lesotho; Primary school in Lesotho